(untitled) (Community Based Medical Journal, 2016)
Down syndrome is the most common congenital abnormality affecting numerous organs including skin and is associated with an increased incidence of alopecia areata. Down syndrome is an extensively researched condition but alopecia areata seldom received appropriate attention. Alopecia areata in Down syndrome is very refractory to treatment and there are only few relevant published data are available in medical literature. Two cases of alopecia areata associated with Down syndrome are presented here. These patients were treated with a short course of prednisolone; a good result was observed in one case but that was unsatisfactory in another case. The disease relapses in both cases within few months of treatment. CBMJ 2016 July: Vol. 05 No. 02 P: 43-46